Empowerment of Micro, Small, and Medium Enterprises in Villages Based on Technology Through Community Service Programs - Sopingi, Imam; Zeffa , Ahmad; Yumna, Hanin (LPPM STAI Darul Falah, 2025)
The community service program titled